Hello.
Step
2. 6x + 29 = 5 (1 point)
–4
–18
204
–144
halpppp pleaseee
2 answers
Hello.
Step 1) Subtract 29 from both sides of the equation.
6x+29-29=5-29.
Step 2) Simplify.
Subtract the numbers.
6x= -24
Step 3) Divide both sides of the equation by the same term.
6×/6 = -24/6
Step 4) Simplify.
Cancel terms that are in both the numerator and denominator.
Divide the numbers.
Divide the following.
-24 ÷ 6 = ????
I will be glad to review your answer.
Step 1) Subtract 29 from both sides of the equation.
6x+29-29=5-29.
Step 2) Simplify.
Subtract the numbers.
6x= -24
Step 3) Divide both sides of the equation by the same term.
6×/6 = -24/6
Step 4) Simplify.
Cancel terms that are in both the numerator and denominator.
Divide the numbers.
Divide the following.
-24 ÷ 6 = ????
I will be glad to review your answer.